2022
DOI: 10.3390/cli10050074
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Trends of Precipitation and Temperature Extremes across the North-East Region of Côte d’Ivoire over the Period 1981–2020

Abstract: The northeast region of Côte d’Ivoire, where agriculture is the main economic activity, is potentially vulnerable to extreme climatic conditions. This study aims to make a comprehensive spatio-temporal analysis of trends in extreme indices related to precipitation and temperature for the Zanzan region of Côte d’Ivoire over the period of 1981–2020. The statistical significance of the calculated trends was assessed using the non-parametric Mann–Kendall test, while Sen’s slope estimation was used to define the am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 68 publications
0
1
0
Order By: Relevance
“…A study published by Isidoro Orlanski in 1975 showed that meteorological properties could behave dynamically at different spatiotemporal scales, showing the dependence that the precipitation forecast has on the climate at different scales (Orlanski, 1975). Recent works have also investigated the spatiotemporal precipitation patterns and how meteorological factors influence this phenomenon in many regions worldwide (Huang et al, 2018;Wood et al, 2021;da Silva et al, 2022;Kouman et al, 2022). A study investigated the effects of SST and geopotential heights in S2S scale precipitation forecasting of the weekly occurrence of extreme precipitation events above 99% over the contiguous USA (Zhang et al, 2023).…”
Section: Temporal Scales and Correlationmentioning
confidence: 99%
“…A study published by Isidoro Orlanski in 1975 showed that meteorological properties could behave dynamically at different spatiotemporal scales, showing the dependence that the precipitation forecast has on the climate at different scales (Orlanski, 1975). Recent works have also investigated the spatiotemporal precipitation patterns and how meteorological factors influence this phenomenon in many regions worldwide (Huang et al, 2018;Wood et al, 2021;da Silva et al, 2022;Kouman et al, 2022). A study investigated the effects of SST and geopotential heights in S2S scale precipitation forecasting of the weekly occurrence of extreme precipitation events above 99% over the contiguous USA (Zhang et al, 2023).…”
Section: Temporal Scales and Correlationmentioning
confidence: 99%
“…With some uses relying on the availability of streamflow which is impacted by climate variability and change [42]. According to [43], rainfall and extreme temperature are also highly variable and could affect how water resources are used in the basin.…”
Section: Study Areamentioning
confidence: 99%
“…Diatta et al [13] studied the extreme precipitation in West Africa and revealed that extreme precipitation in the Sahel was strongly related to the Eastern Mediterranean Sea (EMS), whereas that of the Western and Northwestern Sahel was associated with AMM, MJO8, NINO.3.4, and TAPODI. Kouman et al [14] studied the trend changes of extreme precipitation in the northeast of Côte d'Ivoire in West Africa and showed a decline in the PRCPTOT, SDII, and CWD indices, indicating a decrease in rainfall in the region. Ayugi et al [15] studied extreme precipitation evolution over East Africa toward the end of the 21st century (2081-2100) relative to the baseline period (1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014) and demonstrated that SDII, R95pTOT, R20mm and PRCPTOT indices had significant changes during the OND (October to December) season compared to the MAM (March to May) season.…”
Section: Introductionmentioning
confidence: 99%